DO HEALTH INSURERS CONTRACT THE BEST PROVIDERS? PROVIDER NETWORKS, QUALITY, AND COSTS. (21st February 2019) - Boone, Jan; Schottmüller, Christoph
Abstract: We provide a modeling framework to analyze selective contracting in the health‐care sector. Two health‐care providers differ in quality and costs. When buying health insurance, consumers observe neither provider quality nor costs. We derive an equilibrium where health insurers signal provider quality through their choice of provider network. Selective contracting focuses on low‐cost providers. Contracting both providers signals high quality. Market power reduces the scope for signaling, thereby leading to lower quality and inefficiency.